Reproductive Health Literacy and Fertility Awareness Among Polish Female Students - Chawłowska, Ewelina; Lipiak, Agnieszka; Krzysztoszek, Jana; Krupa, Beata; Staszewski, Rafał (Frontiers in Public Health, 2020)
The falling fertility indicators and high prevalence of infertility in Poland make it important for people of reproductive age to have good knowledge of their own fertility in order to be able to take care of their reproductive health. This paper examines reproductive health literacy and fertility awareness among Polish female students. It can help identify gaps in reproductive health education in Poland. The study group included 456 women aged 18–29, who were students of 6 public universities located in Poznan, Poland. The method used was a survey using a self-developed questionnaire assessing the students' knowledge of female and male fertility-related physiology and fertility patterns. The respondents' knowledge was assessed on the basis of the percentage of correct answers. Regression analysis and univariate analysis of variance were used to explore relationships between the students' knowledge and their age, year of study, university and source(s) of information. The average score of correct answers was 55.8%. Older students and medical university students were the most knowledgeable. 93.4% of the respondents correctly identified the optimum age for a woman to have the first child from the point of view of achieving pregnancy fast. Over 90% of the respondents knew such fertility-compromising risks as smoking, diseases and psychological distress. There was much poorer awareness of the adverse effect of unbalanced diet, irregular sleep, and long-lasting physical effort. 47.1% of the students reported gaining information from a number of sources, but as many as 28.3% said their only source was primary or middle school classes. Reproductive health knowledge among the young female students is incomplete, especially as regards lifestyle-related risks. They should be encouraged to supplement it by consulting reliable sources such as health professionals. It is advisable to ensure that the curricula of medical university students provide thorough knowledge in this area, and to arrange suitable electives for students from other universities. As primary and secondary school classes remain an important source of information, quality teaching at these levels should be offered with a focus on making the knowledge as practical and operational as possible. Relevant graduate, postgraduate and in-service courses should be available to professionals responsible for spreading reproductive health knowledge.